Strategies for enhancing CAR T cell expansion and persistence in HIV infection - Rothemejer, Frederik Holm; Lauritsen, Nanna Pi; Søgaard, Ole Schmeltz; Tolstrup, Martin (Frontiers in Immunology, 2023)
Chimeric Antigen Receptor (CAR) T cell therapies are tremendously successful in hematological malignancies and show great promise as treatment and curative strategy for HIV. A major determinant for effective CAR T cell therapy is the persistence of CAR T cells. Particularly, antigen density and target cell abundance are crucial for the engagement, engraftment, and persistence of CAR T cells. The success of HIV-specific CAR T cells is challenged by limited antigen due to low cell surface expression of viral proteins and the scarcity of chronically infected cells during antiretroviral therapy. Several strategies have been explored to increase the efficacy of CAR T cells by enhancing expansion and persistence of the engineered cells. This review highlights the challenges of designing CAR T cells against HIV and other chronic viral infections. We also discuss potential strategies to enhance CAR T cell expansion and persistence in the setting of low antigen exposure.